Problem Focused Coping sebagai Prediktor Kualitas Hidup pada Family Caregiver Pasien Kanker Payudara - Fairuz, Maulida Ihza; Meiyuntariningsih, Tatik; Aristawati, Akta Ririn (JIWA: Jurnal Psikologi Indonesia, 2025)
Family caregivers play an important role in caring for breast cancer patients. However, their condition has not received much attention, where studies on family caregivers in Indonesia are still limited, especially those related to quality of life. This study aimed to determine the relationship between problem-focused coping and quality of life in family caregivers of breast cancer patients. The research design is a correlational study. The sample of the study was 74 family caregivers of breast cancer patients, obtained from purposive sampling. The sample criteria were limited to family caregivers who were of productive age as students or workers, and had accompanied families with breast cancer for 0-1 year. Problem-focused coping and quality of life were measured using scale constructed by the writer. Data analysis was conducted with Spearman Brown. The result of the study shows a significant positive correlation between the two variables. This shows that the higher tendency of family caregivers to apply problem-focused coping, the higher the level of quality of life.